The Influence of Social Media Marketing Strategies on Consumer Engagement - Tampe Tuah Malem Ginting; Arief Muhazir Insandi (Jurnal Manajemen Bisnis Eka Prasetya, 2024)
This study explores the influence of social media marketing strategies on consumer engagement, a critical aspect for businesses in the digital era. With the increasing reliance on social media platforms as marketing tools, understanding their effectiveness in fostering consumer interaction is paramount. This research employs a literature review method to analyze existing studies, reports, and scholarly articles on the topic, providing a comprehensive overview of how diverse strategies, such as content marketing, influencer collaborations, and targeted advertising, impact consumer behavior and engagement levels. The findings reveal that well-executed social media marketing strategies significantly enhance consumer engagement by fostering brand awareness, loyalty, and emotional connections. Key factors contributing to successful engagement include consistency in posting, authenticity in brand communication, and leveraging interactive features such as polls, quizzes, and live sessions. Additionally, the study identifies the challenges businesses face in implementing these strategies, including algorithm changes, audience segmentation, and competition in the crowded digital marketplace. This research contributes to the growing body of knowledge on digital marketing by providing actionable insights for businesses aiming to optimize their social media strategies. By synthesizing existing literature, this study underscores the importance of aligning social media practices with consumer expectations and emerging technological trends to achieve sustainable engagement.